(3VjGA ef QGe GdhUhd Edi NajGJ gOGjI GdYbhd aj Yde GdCUhds - (3TQa GdTQjYI GdMSf Hf jMji SdGfs; (3GdMSjf Hf GdbGSe Hf eMeO Gdjefj,J (B1050 (3g` s ((3UfYGA s)
(3ChdgG (B:s
(3GdMeO ddg GdPi GaGV YdjfG ef EfYGeg ZGjI GdShd , hOdfG Ydi eYQaJg hJhMjOg HgOGjI GdYbhd s
(3BNQgG (B:s
(3eY bhI GdHMK EdN , aJajO QLMGf YOe GdOdjd hQLMhMg EMJeGd GdhLhO , hGddg CYde HGdUhGH hEdjg GdeQLY hGdeBH hGdMeO ddg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdYfhGfGJ HGdMeQIs
(3Ydi MhGTjgG JYdjbGJ eajOI s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
Keywords: (3Gdabg GdESdGejs